Correlation risk analysis of serum RAGE and HLI levels in patients with immune diseases: Serum RAGE and HLI level in immune diseases - Li, Xin; Zha, Kexin; Xian, Gongxue; Shen, Xueping; Yan, Shengyan; Han, Qiuping (Journal of Medical Biochemistry, 2026)
[Objective]: To explore the roles of Human Leukocyte Interferon (HLI) and Receptor for Advanced Glycation Endproducts (RAGE) in the occurrence and development of systemic lupus erythematosus (SLE), as well as their associations with the disease activity and clinical symptoms of SLE, and to evaluate the clinical application value of their detection. [Methods]: The levels of serum RAGE and HLI in SLE patients were detected via ELISA. The immunomagnetic bead method was used to measure the amounts of interleukin (IL)-1β, IL-2, IL-4, IL-5, and IL-6. Serum HLI and RAGE levels in the active and inactive groups were assessed to gauge the effectiveness of the trial. [Results]: The SLE group had higher levels of HLI and RAGE than the RA group (P<0.05), while the RA group had lower levels of IL-2 and IL-6 (P<0.05). The active group had higher levels of RAGE, IL-6, and HLI than the inactive group (P<0.05). Positive correlations were found between RAGE and HLI (r=0.79, P=0.015) and between RAGE and HLI and the SLEDAI (r=0.65, P=0.016; r=0.44, P=0.034). RAGE is related to the cytokines IL-1β, IL-4 and IL-5, whereas HLI is related to IL-1β and IL-4. [Conclusion]: HLI and RAGE support one another and play a role in the onset and progression of SLE. Both HLI and RAGE are associated with disease activity and clinical manifestations such as fever and kidney damage in patients with SLE. Their detection has great application value in differentiating active and inactive SLE patients in clinical practice.